Exoplanet Transit Spectroscopy of Hot Jupiters Using HST/WFC3. Issue Volume 8:Issue S299(2013) (6th January 2014) - Haynes, Korey; Mandell, Avi M.; Sinukoff, Evan; Madhusudhan, Nikku; Burrows, Adam; Deming, Drake
Abstract: We present analysis of transit spectroscopy of three extrasolar planets, WASP-12 b, WASP-17 b, and WASP-19 b, using the Wide Field Camera 3 (WFC3) on the Hubble Space Telescope (HST). Measurement of molecular absorption in the atmospheres of these planets offers the chance to explore several outstanding questions regarding the atmospheric structure and composition of these highly irradiated, Jupiter-mass objects. We analyze the data for a single transit for each planet, using a strategy similar in certain aspects to the techniques used by Berta (2012), and achieve almost photon-limited results for individual spectral bins. Our final transit spectra are consistent with the presence of a broad absorption feature at 1.4 μm most likely due to water, but the amplitude of the absorption is less than expected based on previous observations with Spitzer, possibly due to hazes absorbing in the NIR. However, the degeneracy of models with different compositions and temperature structures combined with the low amplitude of any features in the data preclude our ability to place unambiguous constraints on the atmospheric composition without a comprehensive multi-wavelength analysis.